Mathematical Proof through Toulmin Argumentation Schema: A SLR in the Context of Mathematics Education - Putri Haryani Syahar; Lukman; Dadang Juandi; Sufyani Prabawanto (Indonesian Journal of Educational Research and Review)
Proof and argumentation are integral components in mathematics education, as argumentation serves as a crucial foundation in constructing mathematical proofs. However, students’ abilities to develop formal arguments often remain limited, particularly in validating the structure and reasoning of proofs. This study aims to evaluate and synthesize findings from previous studies concerning the application of Toulmin Argumentation Schema in mathematical proof within mathematics education contexts. The research employed a Systematic Literature Review (SLR) by analyzing 20 selected articles published in reputable international databases. Data were collected through systematic identification using the PRISMA diagram and thematically analyzed based on research aims, methods, participants, mathematical topics, and key findings. The results indicate that most studies were conducted with secondary school students, undergraduate students, and mathematics teachers, focusing on proof topics such as algebra, geometry, mathematical induction, calculus, and probability. The analysis reveals that students' argument structures typically consist of six elements: data, claim, warrant, backing, rebuttal, and qualifier. The most frequent errors occurred in determining the warrant when validating the type of proof. Furthermore, a hierarchy of proof types was identified, which can guide students in advancing their reasoning and argumentation skills. This review highlights the importance of developing learning strategies and assessment instruments based on Toulmin Argumentation Schema to strengthen students’ mathematical reasoning and proof abilities.